Habitat Requirements of the Florida Panther - Elizabeth F. Pienaar; Elena C. Rubino (EDIS)
The Florida panther (Puma concolor coryi) was listed as endangered under the Endangered Species Act in 1967. Habitat loss and fragmentation are primary threats, driven by urban development and the conversion of rangelands to row crops, citrus production, and mining. This 3-page fact sheet focuses on which habitats are most important for conservation of the Florida panther. Written by Elizabeth F. Pienaar and Elena C. Rubino, and published by the UF Department of Wildlife Ecology and Conservation, October 2014. (Photo courtesy of the Florida Fish and Wildlife Conservation Commission.)